THE MUSLIM RELIGIOSITY, AND ITS RELATION WITH SELF ACTUALIZATION AMONG UNIVERSITY STUDENTS - AHMAD , M; KAMRAN , M (Biological and Clinical Sciences Research Journal, 2024)
This study explores the relationship between intrinsic and extrinsic Muslim religiosity and self-actualization. Additionally, it examines whether demographic factors like gender and educational environment (segregated vs. coeducation) influence these variables. Previous literature suggests religiosity might play a role in personal development, but findings remain inconclusive, especially within specific religious contexts. Objective: To examine the association between intrinsic and extrinsic Muslim religiosity and self-actualization, and to investigate the influence of demographic variables, such as gender and educational environment, on religiosity. Methods: The study utilized a cross-sectional survey design with a sample of 250 participants, of whom 138 (55.2%) were males and 112 (44.8%) were females. Participants’ responses were gathered using the Short Index for Self-Actualization (SISA) and the Muslim Religiosity Scale, which comprised subscales for intrinsic and extrinsic religiosity. Independent sample t-tests were employed to analyze differences in religiosity across gender and educational environments. Pearson’s correlation analysis was used to examine the association between self-actualization and religiosity. Results: Independent sample t-tests indicated no significant differences in intrinsic and extrinsic religiosity based on gender or educational environment. Similarly, Pearson’s correlation analysis revealed no significant correlation between self-actualization and Muslim religiosity (both intrinsic and extrinsic).Conclusion: This study found no significant association between self-actualization and Muslim religiosity, nor did it find significant differences in religiosity based on gender or educational environment. These results suggest that religiosity, whether intrinsic or extrinsic, may not play a distinct role in self-actualization among the participants. Further research is recommended to explore these relationships in broader contexts and diverse populations.